2020
DOI: 10.17214/gaziaot.567544
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation and classification of patients with temporomandibular disorders using ‘Diagnostic Criteria for Temporomandibular Disorders’

Abstract: OBJECTIVE: The aim of the study was to evaluate the frequency of subgroups in a clinical setting of the patients with temporomandibular disorders (TMD) using 'Diagnostic Criteria for Temporomandibular Disorders (DC/TMD)'. MATERIALS AND METHOD: A total of 128 patients with TMD (92 females and 36 males, mean age 33.5 ± 8.28) were involved in the study. DC/TMD Axis I diagnosis criteria was used for the clinical examination of pain disorders and temporomandibular joint (TMJ) disorders. Also, in DC/ TMD Axis I, The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Finally, in our study, the effect of age on muscle pain disorders seemed to be non-significant [55]. This study has some important limitations due to the sampling technique that could have introduced important selection bias, as suggested by the highly unbalanced gender ratio and wide range of age observed.…”
Section: Discussioncontrasting
confidence: 52%
“…Finally, in our study, the effect of age on muscle pain disorders seemed to be non-significant [55]. This study has some important limitations due to the sampling technique that could have introduced important selection bias, as suggested by the highly unbalanced gender ratio and wide range of age observed.…”
Section: Discussioncontrasting
confidence: 52%
“…Temporomandibular disorders (TMD) occur because of problems with the temporomandibular joints and the masticatory muscles. 1 The etiology of TMD is multifactorial and numerous risk factors have been reported in the litera ture. Trauma, anatomical differences, genetic predisposi tion, the psychological status, and parafunctional habits are among the TMD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of pain intensity, global scores and PHQ-9 scores observed in the DC/TMD Axis II assessment provide insights into the psychosocial aspects of TMD, as well as the associated pain-related impairment and chronic pain dysfunction. 35 It is observed that these symptoms are higher in clear aligner patients using intermaxillary elastics compared to clear aligner patients who do not use intermaxillary elastics. Although the experimental group showed a higher depression level than the control group, anxiety and parafunction levels were higher in the control group.…”
Section: Discussionmentioning
confidence: 95%
“…Also, numerous studies have repeatedly demonstrated that individuals with chronic TMD have elevated scores on psychiatric assessments, specifically on Axis II. [35][36][37] Furthermore, previous research has indicated that psychological factors are predictive of an increased risk for TMD. 36,38,39 Additionally, employing Axis II evaluation, specifically through the DC/TMD, for the purpose of psychosocial assessment might be beneficial in informing clinical TA B L E 5 Evaluation of groups in terms of calculated scores according to worksheet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation